1997
DOI: 10.1007/bf02803903
|View full text |Cite
|
Sign up to set email alerts
|

Electrophoretic separation of proteolytic enzymes in pancreatic juice collected with the pouch or catheter method

Abstract: This qualitative enzyme assay indicated that a considerable amount of chymotrypsin C, anodal trypsin, chymotrypsins A and B, elastase II, and cathodal trypsin were present in samples of nonactivated pancreatic juice from PM pigs. In contrast, the only active enzymes identified in pancreatic juice from CM pigs were very small amounts of chymotrypsin A and elastase II. The amounts of chymotrypsin C and cathodal trypsin were lower in activated than in nonactivated pancreatic juice from PM pigs. However, there wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1997
1997
2000
2000

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Therefore for illustrative purposes, we recommend the comparison studies: pouch vs Thomas method (Lee et al, 1986) and pouch vs Routley's method (Gabert et al, 1996(Gabert et al, , 1997 undertaken in the same laboratory. Lee et al (1986) (Kiela et al, 1996).…”
Section: Exposure Of Duodenal Papillamentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore for illustrative purposes, we recommend the comparison studies: pouch vs Thomas method (Lee et al, 1986) and pouch vs Routley's method (Gabert et al, 1996(Gabert et al, , 1997 undertaken in the same laboratory. Lee et al (1986) (Kiela et al, 1996).…”
Section: Exposure Of Duodenal Papillamentioning
confidence: 99%
“…Lee et al (1986) (Kiela et al, 1996). Electrophoretic separation of proteolytic enzymes showed that in the pancreatic juice collected using pouch method the proteolytic enzymes are near fully active or fully active (Gabert et al, 1997 (Guilloteau et al, 1985, Le Dr6an et al, 1997 …”
Section: Exposure Of Duodenal Papillamentioning
confidence: 99%